2019
DOI: 10.1007/s42797-019-00003-8
|View full text |Cite
|
Sign up to set email alerts
|

Marine accident learning with fuzzy cognitive maps (MALFCMs) and Bayesian networks

Abstract: Addressing safety is considered a priority starting from the design stage of any vessel until end-of-life. However, despite all safety measures developed, accidents are still occurring. This is a consequence of the complex nature of shipping accidents where too many factors are involved including human factors. Therefore, there is a need for a practical method, which can identify the importance weightings for each contributing factor involved in accidents. As a result, by identifying the importance weightings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In de Maya et al (2019), historical data for maritime accidents involving UK vessels worldwide and all vessels operating in UK territorial waters between 2011 and 2016 was obtained and analyzed. Thus, general cargo vessels were selected due to the higher number of data entries when compared with other vessel categories, and nine HFs were identified as highly contributing into maritime accidents, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In de Maya et al (2019), historical data for maritime accidents involving UK vessels worldwide and all vessels operating in UK territorial waters between 2011 and 2016 was obtained and analyzed. Thus, general cargo vessels were selected due to the higher number of data entries when compared with other vessel categories, and nine HFs were identified as highly contributing into maritime accidents, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…For the purpose of this case study, marine accidents involving UK vessels worldwide and all vessels operating in UK territorial waters between 2011 and 2016 were analyzed. In addition, grounding/stranding accidents in general cargo vessels were selected for this study due to the higher number of data entries when compared with other accidents and vessel categories, as highlighted in de Maya, Babaleye, and Kurt (2019).…”
Section: Data Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the review of 41 accident investigation reports, Schroder-Hinrichs et al (2011) found that organisational factors were not identified by maritime accident investigators to the extent which the IMO guidelines expected. In addition, Fuzzy Cognitive Map (FCM)-based technique (de Maya et al 2019) was applied to generating weight the importance of human factors as prior failure probabilities, which helped create the BN model. The accident scenario analysis showed that the lack of safety culture contributed the most to the system failure.…”
Section: Accident Investigation In Maritime Transportationmentioning
confidence: 99%